2000
DOI: 10.1007/s001920070027
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral Ultrasonography: Correlation of Urethral Anatomy with Functional Urodynamic Parameters in Stress Incontinent Women

Abstract: To determine whether differences in functional urodynamic parameters can be explained by changes in urethral anatomy, 39 patients underwent intraurethral ultrasonography to obtain a 360 degree view of the urethra. The point of maximal rhabdosphincter thickness was identified in all patients. The thickness, circumference and area of the urethral smooth and skeletal muscle layers were calculated. Data from patient histories and urodynamic evaluations were compared with this anatomical survey. The urodynamic diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…On the basis of previous work correlating urethral sphincter morphologic characteristics with functional urodynamic parameters, 8 several different measurements were taken ( Figure 3). The diameters of the urethra and longitudinal smooth muscle were measured along a line passing through the transducer's center to the calipers positioned on the outer surface of each structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of previous work correlating urethral sphincter morphologic characteristics with functional urodynamic parameters, 8 several different measurements were taken ( Figure 3). The diameters of the urethra and longitudinal smooth muscle were measured along a line passing through the transducer's center to the calipers positioned on the outer surface of each structure.…”
Section: Methodsmentioning
confidence: 99%
“…8 The results showed that healthy subjects had thicker rhabdosphincters than did subjects with genuine stress incontinence, and subjects with genuine stress incontinence had thicker rhabCorrespondence to: M. Heit…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…De même, Kuo, par voie transrectale, observe dans l'IUE de type III démontrée par des études VUD une diminution de la couche périphérique hypoéchogène assimilée au muscle strié comparativement aux sujets sans incontinence [36]. D'autres études échographiques avec doppler couleur ou par voie intra-urétrale s'attachent à étudier les modifications morphologiques du sphincter urétral mais ne débouchent pas actuellement sur une utilisation pratique [35,[37][38][39].…”
Section: éTude Morphologique Du Sphincter Urétralunclassified
“…For example, transurethral ultrasound of the urethra can be combined with functional tests, such as EMG, to better understand the structure and functioning of the urethra [Fischer et al, 2000]. Ultrasound can also be compared with urodynamic ¢ndings [Heit, 2000], although studies of this nature may prove disappointing, not because of limitations associated with the imaging tests but because of limitations of urodynamic testing. It is even possible to combine functional and imaging tests, much as positron emission tomography (PET) scanning accomplished for central neuroanatomy and function.…”
Section: To Correlate Structure With Function To Understand Normal Phmentioning
confidence: 99%